Physiologically personalized coronary blood flow model to improve the estimation of noninvasive fractional flow reserve. Issue 1 (7th December 2021) - Liu, Xiujian; Xu, Chuangye; Rao, Simin; Zhang, Ye; Ghista, Dhanjoo; Gao, Zhifan; Yang, Guang
Abstract: Purpose: Coronary outlet resistance is influenced by the quantification and distribution of resting coronary blood flow. It is crucial for a more physiologically accurate estimation of fractional flow reserve (FFR) derived from computed tomography angiography (CTA), referred to as FFRCT. This study presents a physiologically personalized (PP)‐based coronary blood flow model involving the outlet boundary condition (BC) and a standardized outlet truncation strategy to estimate the outlet resistance and FFRCT. Methods: In this study, a total of 274 vessels were retrospectively collected from 221 patients who underwent coronary CTA and invasive FFR within 14 days. For FFRCT determination, we have employed a PP‐based outlet BC model involving personalized physiological parameters and left ventricular mass (LVM) to quantify resting coronary blood flow. We evaluated the improvement achieved in the diagnostic performance of FFRCT by using the PP‐based outlet BC model relative to the LVM‐based model, with respect to the invasive FFR. Additionally, in order to evaluate the impact of the outlet truncation strategy on FFRCT, 68 vessels were randomly selected and analyzed independently by two operators, by using two different outlet truncation strategies at 1‐month intervals. Results: The per‐vessel diagnostic performance of the PP‐based outlet BC model was improved, based on invasive FFR as reference, compared to the LVM‐based model: (i) accuracy/sensitivity/specificity: 91.2%/90.4%/91.8% versus 86.5%/84.6%/87.6%, for the entire dataset of 274 vessels, (ii) accuracy/sensitivity/specificity: 88.7%/82.4%/90.4% versus 82.4%/ 76.5%/84.0%, for moderately stenosis lesions. The standardized outlet truncation strategy showed good repeatability with the Kappa coefficient of 0.908. Conclusions: It has been shown that our PP‐based outlet BC model and standardized outlet truncation strategy can improve the diagnostic performance and repeatability of FFRCT.